2019
DOI: 10.1186/s12879-019-4038-8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of high-risk HPV types among women in Sichuan province, China: a cross-sectional study

Abstract: Background Persistent infection with high-risk human papillomavirus (HR-HPV) is a major cause of cervical intraepithelial neoplasia and invasive cervical cancer. We investigated the prevalence of HR-HPV infection and distribution of viral genotypes among women in this area. Methods Women in Sichuan older than 20 years were screened for cervical cancer between January 2015 and December 2016 using liquid-based cytology testing and a flow cytometry-fluorescence hybridizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
26
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 39 publications
(41 reference statements)
7
26
4
Order By: Relevance
“…By further analyzing of population, we found HPV infection prevalence of HEC group is significantly lower than that of OGOC group, which is 15.29% and 37.62% respectively. Among the HPV studies related to Sichuan Province, there is only one focused on the HEC population, and the prevalence of HPV infection is 12.6% [9]. But this study only calculated the high-risk HPV, which may result in the lower prevalence rate than ours.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…By further analyzing of population, we found HPV infection prevalence of HEC group is significantly lower than that of OGOC group, which is 15.29% and 37.62% respectively. Among the HPV studies related to Sichuan Province, there is only one focused on the HEC population, and the prevalence of HPV infection is 12.6% [9]. But this study only calculated the high-risk HPV, which may result in the lower prevalence rate than ours.…”
Section: Discussionmentioning
confidence: 74%
“…The prevalence of neighboring southwest provinces is 26.2% in Chonqing, 16.95% in Guizhou, 12.9% in Yunnan [16][17][18]. For Sichuan, the fourth largest population province located in southwestern China, several studies have investigated its HPV epidemiology and genotype distribution, but the HPV infection prevalence varies, ranging from 10.15-31.3% [7][8][9][10][11][12]. In our study, the HPV infection prevalence of the total population is 23.84%, which is basically consistent with the result of Li et al (24.1%) [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HPV infection rate in the Health Management Center was 14.4% which was lower than that in Guangdong (17.25%) [20]. The prevalence of HR-HPV infection was 11.7%, which was nearly similar to that in Sichuan (12.6%) [21]. The cause of this may be the close geographical location of Chongqing and Sichuan and the similar laboratory detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this variation maybe because of the study period and participants. The most prevalent types of HR-HPV infection in Health Management Center were HPV52, 58, 53, 16 in this order, different from the types in Sichuan (HPV52, 53, 58, 16 in this order) [21]. Some studies have reported that HPV 52 and 58 were more dominant genotypes and relate to cervical cancer occurrence in the Asian population [22][23][24].…”
Section: Discussionmentioning
confidence: 99%